Hydraulika potrubních sítí ve vzduchotechnice - Bernard, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Diplomová práce řeší hydraulické vlastnosti vybraných typů tvarovek určené pro vzduchotechnické rozvody, především tlakové ztráty jednotlivých tvarovek. Dále se v projektové části zaměřujeme na porovnání daných tvarovek s běžným systémem rozvodů spiro potrubí.

This diploma thesis describes hydraulic properties of specific types of fittings designed to HVAC systems with primary focus on pressure losses of these fittings. We are focusing on comparison of specific fittings with usual systems of spiro pipes in the project part of this thesis.
Hydraulic of pipeline network in ventilation systems
Keywords: hydraulika; Bernoulliho rovnice; koleno; turbulentní proudění; laminární proudění; místní ztráty; ztráty třením; hydraulics; Bernoulli's principle; bend; turbulent flow; laminar flow; local losses; friction losses